Constructing Optimal Futures for Education - Technology Foresight in Educational Policy and Planning - Tryggvi Thayer (Universitetsforlaget, 2014)
Abstract This article focuses on challenges associated with the use of technology foresight for developing long-term strategies for innovative uses of ICT in education with an emphasis on the role of creativity. The outcomes of two international foresight programmes on the future of education are critically examined. The findings demonstrate the need to address programme participants' capacity to engage in systematic futures thinking and to emphasise creative aspects of constructing shared visions of the future.